Cavernous venous malformations of the orbit (so-called cavernous haemangioma): a comprehensive evaluation of their clinical, imaging and histologic nature. Issue 7 (13th March 2014) - Rootman, Dan B; Heran, Manraj K S; Rootman, Jack; White, Valerie A; Luemsamran, Panitee; Yucel, Yeni H
Abstract : Purpose: The purpose of this investigation is to describe the clinical, imaging, histologic and flow dynamic characteristics of orbital cavernous haemangioma. Methods: In this clinicopathologic series, clinical features were obtained from patient records. All imaging studies were reviewed. All specimens were reviewed with haematoxylin and eosin, and 10 were subject to a staining protocol including: Movat Pantachrome, periodic acid Schiff, D2-40, CD31, GLUT-1, Ki-67, vascular endothelial growth factor receptor 1 (VEGF-r1) (flt-1), VEGF-r2 (Flk-1), VEGF, anti-smooth muscle actin (SMA), CD20, CD4, CD8 and CD68. Imaging and pathology were reviewed in a systematic fashion. Results: Clinically, lesions were more common in middle-aged females presenting with axial proptosis and pain. One-third demonstrated signs of optic nerve dysfunction. Dynamic imaging revealed focal early and diffuse late enhancement. Lesions demonstrated slow growth at 0.2 cm 3 /year. Histologically, all lesions demonstrated large vascular channels with mature-appearing endothelium and abundant stroma. Three salient features were noted and characterised: thrombosis, nests of perivascular hypercellularity and expanded stromal elements. Acute thrombosis was a feature of each specimen (<10% of channels). Fibrin clots were lined by a layer of CD31+ endothelium. Perivascular hypercellular areas stained uniformly with CD31 and less so with VEGFr2. Additionally, focal areas of Ki67+ and CD68+ cells were found in these regions. Expanded stroma contained CD31+ microcapillary networks and stained diffusely with anti-SMA. Conclusions: Cavernous haemangioma demonstrate clinical features and growth characteristics of a benign mass. Dynamic imaging highlights their slow flow vascular nature. Histologically, the hypercellularity and stromal changes identified can be understood within the pathogenic context of thrombosis and recanalisation in an organised lesion.